The Role of an Early Childhood Community Health Worker in Addressing Psycho-Social Needs in the Perinatal and Early Childhood Period - Sahar Moheize; Mandy Hsu; Luz Adriana Matiz; Patricia Peretz; Kristy Medina; Amanda Esteves; Dodi Meyer; Beth Maletz; Lucie Pineda; Evelyn Berger-Jenkins (SAGE Publishing, 2024)
Objective: Addressing family psychosocial and mental health needs in the perinatal and early childhood period has a significant impact on long-term maternal and child health and is key to achieving health equity. We aimed to (1) describe and evaluate the role of an Early Childhood Community Health Worker (EC-CHW) to address psychosocial needs and improve psychosocial well-being for families in the perinatal period, and (2) examine factors associated with completion of goals. Methods: An EC-CHW program was modeled after an existing hospital CHW program for children with special healthcare needs and chronic disease. An evaluation was conducted using repeated measures to assess improvements in psychosocial outcomes such as family stress and protective factors after participating in the EC-CHW program. Linear regression was also used to assess factors associated with completion of goals. Results: Over a 21-month period (January 2019-September 2020), 161 families were referred to the EC-CHW. The most common reasons for referral included social needs and navigating systems for child developmental and behavioral concerns. There were high rates of family engagement in services (87%). After 6 months, families demonstrated statistically significant improvements in protective factors including positive parenting knowledge and social support. Only 1 key predictor variable, maternal depression, showed significant associations with completion of goals in the multivariable analysis. Conclusions: This study demonstrated the need for, and potential impact of an EC-CHW in addressing psychosocial and mental health needs in the perinatal period, and in a primary care setting. Impacts on protective factors are promising.